Effects of Carbonization Temperature on Mechanical and Thermal Insulation Properties of Carbon Aerogel Composites using Phenolic Fibers as Reinforcement. (12th February 2023) - Li, Longlong; Liu, Fengqi; Feng, Junzong; Jiang, Yonggang; Li, Liangjun; Feng, Jian
Abstract : A series of carbon fiber-reinforced carbon aerogel composites (C/CAs) were prepared via carbonizing phenolic fibers impregnated organic aerogel at temperatures ranging from 1, 000 to 1, 600°C. Phenolic fiber as soft reinforcement shrinks synchronously with the aerogel matrix during the preparation process, which effectively avoided microcracks and achieved an excellent reinforcement effect. The effects of carbonization temperatures on the mechanical and thermal insulation properties of the C/CAs were investigated via pore structural and morphological analysis, as well as the characterization of mechanical strength and thermal conductivity. The results show that the compressive strength of C/CA is 1.26–2.14 MPa in xy -direction and 0.55–1.20 MPa in z -direction. The obtained bending strength range from 1.92 to 3.62 MPa with the carbonization temperature increase from 1, 000 to 1, 600°C. The thermal conductivity of C/CA-1000 at 1, 800°C is 0.1637 W·m −1 ·K −1 while that of reached 0.2713 W·m −1 ·K −1 of C/CA-1600. Further study found that the change of porosity and pore size caused by the closure of micropores at high temperatures should be responsible for performance evolution.